Profil Keterampilan Berpikir Kreatif Siswa SMA Negeri 1 Karangrayung pada Konsep Fluida Statis - Paryumi Paryumi (Perkumpulan Kualitama Edukatika Indonesia, 2022)
To achieve the goals of national education, students are required to: have creative thinking skills, especially in physics subjects. This study aims to determine the profile of creative thinking in class XI students of SMA Negeri 1 Karangrayung on static fluid material for the academic year 2022/2023. The research subjects were 36 students of class XI SMA Negeri 1 Karangrayung. The research method used is descriptive quantitative. The variable of this research is creative thinking skills measured through a written test in the form of essay questions. Data collection uses questions developed from four creative thinking indicators, each question is given a score of 1-4 with the criteria of each indicator. Based on the results of the study, the creative thinking ability of students of SMA Negeri 1 Karangrayung, Grobogan Regency was 22.55 or 51% of the maximum score of 44, included in the very poor category. When viewed from the ability of students based on indicators of fluency, 2.22 (56%) is in the poor category, flexibility is 2.56 (64%), in the sufficient category, authenticity is 1.63 (38%), in the very category, and the detail/elaboration of 1.5 (19%), in the very poor category. The results of the achievement of students' creative thinking skills need to be further improved in the learning process.